How Anticipated and Experienced Stigma Can Contribute to Self-Stigma: The Case of Problem Gambling - Hing, Nerilee; Russell, Alex M. T. (Frontiers in Psychology, 2017)
The degree to which anticipated and experienced public stigma contribute to self-stigma remains open to debate, and little research has been conducted into the self-stigma of problem gambling. This study aimed to examine which aspects of anticipated and experienced stigma (if any) predict the anticipated level of public stigma associated with problem gambling and the degree of self-stigma felt by people experiencing problem gambling. An online survey of 177 Australians experiencing problem gambling examined whether aspects of the public characterization of problem gambling, anticipated reactions to problem gamblers, and experiences of devaluation and discrimination predicted anticipated level of public stigma and self-stigma. The study found that self-stigma increases with expectations that the public applies a range of negative stereotypes to people with gambling problems, holds demeaning and discriminatory attitudes towards them, and considers them to lead highly disrupted lives. These variables directly predicted anticipated level of public stigma and indirectly predicted self-stigma. These findings lend weight to conceptualizations of self-stigma as an internalization of actual or anticipated public stigma. They also highlight the need for stigma reduction efforts, particularly those that lower negative stereotyping and prejudicial attitudes, to improve currently low rates of help-seeking amongst people with gambling problems.